2020
DOI: 10.3389/fpls.2020.618491
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drought on Transcriptome and Hormonal Profiles in Barley Genotypes With Contrasting Drought Tolerance

Abstract: Like many cereal crops, barley is also negatively affected by drought stress. However, due to its simple genome as well as enhanced stress resilient nature compared to rice and wheat, barley has been considered as a model to decipher drought tolerance in cereals. In the present study, transcriptomic and hormonal profiles along with several biochemical features were compared between drought-tolerant (Otis) and drought-sensitive (Baronesse) barley genotypes subjected to drought to identify molecular and biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 145 publications
(161 reference statements)
10
25
0
Order By: Relevance
“…Studies have shown that there is little intersection between ABA-induced differentially expressed genes and key differentially spliced genes [ 67 ]. The stress-induced transcriptome results of wheat and rice are consistent with the results [ 16 , 87 ]. This suggests that AS is an independent mechanism by which ABA regulates plant growth and environmental responses.…”
Section: Aba Mediates Plant Development and Abiotic Stress Via Altern...supporting
confidence: 89%
“…Studies have shown that there is little intersection between ABA-induced differentially expressed genes and key differentially spliced genes [ 67 ]. The stress-induced transcriptome results of wheat and rice are consistent with the results [ 16 , 87 ]. This suggests that AS is an independent mechanism by which ABA regulates plant growth and environmental responses.…”
Section: Aba Mediates Plant Development and Abiotic Stress Via Altern...supporting
confidence: 89%
“…Another widely used method to identify drought-associated genes is to analyze gene expression profiles at the transcriptional level of the drought-resistant and sensitive line exposed to drought stress [79][80][81]. Barley transcriptomic data reported differentially expressed genes in drought-tolerant and sensitive genotypes, in relation to terminal drought stress.…”
Section: Qtl Gwas and Other Studies To Identify New Genetic Resources Of Tolerance To Droughtmentioning
confidence: 99%
“…MYB genes encode another class of TFs known for their involvement in the regulation of drought stress responses [99]. Harb et al [79] reported that NAC transcription factors are specifically induced in drought-tolerant barley compared to sensitive genotype. The improvement roles of NAC genes in response to the drought stress have been reported previously [100].…”
Section: Qtl Gwas and Other Studies To Identify New Genetic Resources Of Tolerance To Droughtmentioning
confidence: 99%
“…Seed ethylene priming allowed the recall of long-lasting stress defensive memory, which decreased the Ethylene perception signal's gene expression. The Ethylene perception signal and root to shoot ABA secondary signal involve a dialogue between ABA, IAA, and SA, and the ABA is the dominant hormone regarding its role in plant drought tolerance (Wang et al 2017b;Zhu et al 2019;Harb et al 2020). The production of ABA in the root hair and then mobilized to the leaves will maintain plant water status through stromal regulation (Zhang et al 2018), and then postpone the development of water de cit in the aboveground (Liu et al 2005).…”
Section: Seed Ethylene Priming Recalling Long-lasting Stress Memory Tmentioning
confidence: 99%
“…The root to leaf ABA signal is the crucial factor for stomatal regulation that ensures the stomatal CO 2 exchanges and leaf water loss in a balanced state (Tombesi et al 2015). At the molecular level, these defense mechanisms have been reportly modulated by the transcription factors and phytohormone signal transduction pathways, which further regulate root osmolyte levels by triggering sugar catabolism, regulating stomatal closure by transducing root to leaf ABA signaling, increasing cell antioxidants level by activating the ROS defense system (Wang et al 2021;Harb et al 2020;Li et al 2019). Although the short-term adaption of plants to drought stress has been clari ed, the knowledge of long-term drought stress memory is more valuable for avoiding nal grain yield loss by soil water de cit.…”
Section: Introductionmentioning
confidence: 99%